Consequences of Diseases Caused by Airborne Infections (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The problems of epidemiology and immunization among the population and military personnel of airborne “children” (measles, mumps, rubella and etc.) and other common infections (influenza, meningococcal and streptococcal infections, acute respiratory diseases and pneumonia). Ways to improve calendars of preventive vaccinations for military personnel, including for epidemic indications, were discussed. as well as the need to immunize risk groups against influenza, meningococcal, pneumococcal, adenoviral infections and chickenpox, and in the future - against other current airborne infections, including "children's". Risk of disease from airborne droplets the route of transmission of infection will increase in the case of close contact, but not everyone gets sick, and the diseases progress differently. This is determined primarily by the state of human immunoresistance to pathogens circulating in communities autonomously or introduced from outside. Among of the mentioned categories of the population is always available a significant proportion of individuals with a deficiency of immunoresistance, manifested by a predisposition to frequent diseases of VCI, which is genotypically and/or phenotypically determined. This share depends on the number of groups, the age of people and the conditions of their life and activities. Typically, the autumn-winter-spring wave of VCI incidence is the main one, the summer wave is less intense, but in military training centers the latter is also very impressive: it is reflected in the large number of teams and the renewed composition. Sometimes an increase in incidence of different etiologies occurs almost simultaneously, but more often first - ARI, then tonsillitis, and later - by other VKIs.